Ethanol Extract of the Infructescence of Platycarya strobilacea Sieb. et Zucc. Induces Methuosis of Human Nasopharyngeal Carcinoma Cells. (29th April 2020) - Liu, Jinkun; Ying, Min; Wu, Bin; Fu, Chaomei
Abstract : The infructescence of Platycarya strobilacea Sieb. et Zucc. (PS) has been used in the treatment of rhinitis and sinusitis in clinical practice. Our preliminary study showed that an ethanol extract of the infructescence of PS (EPS) had significant antinasopharyngeal carcinoma (NPC) effects in vitro. However, the mechanism underlying the NPS cell death induced by EPS remains unclear. The aim of the present study was to investigate the inhibitory effects of EPS on NPC cells and to elucidate the underlying mechanism. The effects of EPS on NPC cells were investigated in CNE1 and CNE2 cells in vitro. In EPS-treated cells, the cell morphological changes were evaluated through fluorescence microscope, transmission electron microscopy, and flow cytometry. The underlying mechanism was analyzed via network pharmacology and further verified by western blot analysis. The anticancer effects of EPS were associated with the generation of CNE1 and CNE2 cell fusion and vacuoles, the perturbation of lysosomal vesicle transportation, and the induction of methuosis. The network pharmacology and western blot results indicated that the effect of EPS in NPC cells might be achieved via regulation of the Ras proto-oncogene (RAS)/mitogen-activated protein kinase (MAPK) signaling pathway and the transcription factor c-Fos proto-oncogene (c-FOS) and its downstream genes. EPS induces NPC cell death through methuosis. The mechanism might be related to regulation of the transcription factor c-FOS and its downstream genes.